(untitled) (Neo Science Peer Reviewed Journal, 2024)
Hepatocellular carcinoma (HCC) is the third most prevalent cause of cancer-related death worldwide and the fifth most common cancer with an annual incidence of over 500,000 cases worldwide [1,2]. The cirrhosis that underlies the great majority of HCC tumors is most frequently caused by alcohol-related liver disease, hepatitis B or hepatitis C virus infection, or nonalcoholic fatty liver disease (NAFLD). HCC still has a dismal five-year survival rate of 15% despite recent therapy improvements, such as the use of Atezolizumab + Bevacizumab for unresectable HCC. These factors are mostly attributable to delayed diagnosis and the poor effectiveness of current therapies [3, 4].